Penerapan Metode Analytical Hierarchy Process (AHP) Dalam Pemilihan Karyawan Berprestasi Berbasis Web Pada PT. Dambosko Bronton - Nisa, Anisa Damayanti Daulay; Yandra Niska, Debi (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
Human resources are very important in achieving the vision and mission of the company called employees. Currently PT. Dambosko Bronton does not yet have a selection program for outstanding employees so that the lack of employee work motivation, the unavailability of computerized methods and systems that support the selection of outstanding employees are still obstacles so that they are considered less effective. Web-based systems that use AHP should be designed to address these issues, so that systems are built more effectively and speed up the process of selecting outstanding employees. Decision retrieval uses the AHP method because this method uses human perception as the main input. This research aims to facilitate HRD in making the right decisions and accelerate the decision-making process. Keywords: Decision support system, AHP method, Selection of outstanding employees.